A Study on Clinical Characteristics and The Impact Of Covid-19 In Hemodialysis Patients - Towseef Ahmad Sofi; Ibtisam Nazir Khan; Pankaj Kaul (International Journal of Biomedical Innovations and Engineering, 2025)
Background: The Corona Viruses Disease-19 pandemic has severely impacted Hemodialysis patients, who are vulnerable due to compromised immune systems and underlying comorbidities. Frequent Dialysis center visits increase their exposure risk to severe acute respiratory syndrome- Coronavirus Disease, and chronic inflammation, uremia, and immunosenescence may impair their immune response. Methods: This retrospective study included 60 Hemodialysis patients diagnosed with COVID-19 between January -July 2024. Data on demographics, clinical characteristics, laboratory results and outcomes were collected from electronic medical records. Patients were followed until recovery or death. Descriptive statistics and logistic regression analysis were applied to determine the risk factors associated with severe disease and mortality. Results: 15 patients (25%) presented with asymptomatic or mild symptoms, 12 patients (20%) exhibited moderate symptoms, and 19 patients (31.66%) developed severe symptoms. A total of 22 patients (36.66%) did not require admission for severe care, while 7 patients (11.66%) accounted for mortality cases. Risk factors for both severe COVID-19 and mortality were advanced age; number of comorbidities; cardiovascular diseases; increased levels of aspartate transaminase, lactate dehydrogenase, blood urea nitrogen/creatinine ratio, brain natriuretic peptide, and red cell distribution and decreased levels of hematocrit and albumin. Moreover, the number of COVID-19 vaccinations was a protective factor against both severe disease and mortality. Conclusion: COVID-19 in Hemodialysis patients is associated with high morbidity and mortality. Early recognition, isolation and aggressive management are crucial to improving outcomes in this vulnerable population.
Keywords: COVID-19; clinical characteristics; hemodialysis; mortality; outcomes